Lexicographie et enseignement de langues liées Ã l'immigration: note sur le contexte sociolinguistique de l'élaboration du dictionnaire finnois–lingala–franÃ§ais - Batumona Adi Gilbert, Kadima (Lexikos, 2013)
Lexicography and Language Teaching Related to Immigration: Note on the Sociolinguistic Context of the Development of the Finnish–Lingala–French Dictionary. The Finnish–Lingala–French Dictionary discussed in this article was compiled within the context of immigration. It illustrates the support for migrants in their host country under the right to language recognized for every human being and under international law establishing the cultural rights of migrants. Our contribution to this issue, intended to be linguistic, addresses some aspects of the cultural rights of migrants whereby their recognition has resulted in a lexicographical activity concerning Lingala whose presence in Finland can only be explained because of immigration.